Evaluation of E-Budgeting Implementation in Planning Budget in Maros Regency - Lulu Qurrata A'yun; Nursaleh Hartaman (Journal of Government and Political Issues, 2021)
Several Regional Governments then implemented E-Budgeting in the preparation of the budget. One region that has implemented E-Budgeting in preparing regional budgets is Maros Regency. The research in this paper was conducted by reviewing literature, articles and using secondary data with documentation from observations via the internet. The data was obtained by monitoring the government website and the application used by the Maros Regency Government in conducting the E-Budgeting process and then conducting a descriptive qualitative analysis. The results of the study show that evaluation of the implementation of the E-Budgeting System in Budgeting in Maros Regency can be stated that at this time the electronic-based budgeting system has been implemented well but has not been fully optimal in achieving the results and benefits, this can be seen in 6 (six) criteria in the evaluation, namely effectiveness, efficiency, adequacy, equity, and responsiveness.